ROTASI “RODA KESEHATAN LANSIA” SEBAGAI STRATEGI LATIHAN FISIK UNTUK MENGURANGI RISIKO JATUH PADA LANSIA - Putri, Linta Meyla; Kristiani, Rina Budi; Mamesah, Marline Merke (PPM STIKES Adi Husada, 2025)
Introduction & Aim: Elderly individuals experience various physical changes, including balance disorders and declining vision function, which increase the risk of falls. Falls among the elderly have become a major health concern that can significantly reduce their quality of life. Therefore, appropriate interventions, such as physical exercise, are necessary to help reduce the risk of falls. This program aims to improve balance and reduce fall risks among the elderly through a structured exercise program using the